The Effectiveness of Teachers' Roles in Supporting Learning for Students with Special Needs in Inclusive Classes - Malizal, Zelynda Zeinab; Rizqi, Putri Umrottur (Indonesian Scientific Publication, 2025)
This study explores the effectiveness of teachers' roles in supporting the learning of students with special needs (ABK) in inclusive classes. Using a qualitative approach and case study method, data were collected through in-depth interviews, direct observation, and documentation in three inclusive schools in Indonesia and Malaysia. The research findings show that teachers are strategically motivators, facilitators, initiators, and mediators in supporting ABK learning. Teachers can modify the curriculum, teaching strategies, and classroom management based on students' individual needs. In addition, initial assessments are used to analyze student abilities so that learning can be adjusted. Teachers also utilize positive reinforcement, emotional validation, and personal guidance to increase learning motivation. The use of technology, such as TV and LCD, as well as creativity in creating simple learning media, also supports learning success. This study found that collaboration between regular teachers, special education teachers, and parents plays an important role in creating a conducive learning environment. This study contributes by adding perspectives on a holistic approach that integrates academic, social, and emotional aspects in inclusive education. Practical implications include the need for ongoing inclusive teacher training and the development of policies that support the management of inclusive education.